1995
DOI: 10.1111/j.1574-6976.1995.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototaxis and other sensory phenomena in purple photosynthetic bacteria

Abstract: The mechanisms employed by purple photosynthetic bacteria to convert light to utilizable chemical energy have been a major focus of research over the past 50 years. Utilization of light by photosynthetic bacteria for other purposes, however, has received relatively little attention. The recent discovery of phototaxis by Rhodospirillum centenum provides new opportunities for biochemical and molecular biological analysis of sensory processes in purple bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In contrast to individual cell movement in liquid media, the purple phototrophic bacterium Rhodospirillum centenum exhibits phototaxis of colonies on soft (0.8%) agar, driven by a lateral flagellum (14). Such photoresponsive behavior in purple phototrophic bacteria was thought to be unique to R. centenum (8,16), although some species of cyanobacteria are capable of phototaxis (5, 7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to individual cell movement in liquid media, the purple phototrophic bacterium Rhodospirillum centenum exhibits phototaxis of colonies on soft (0.8%) agar, driven by a lateral flagellum (14). Such photoresponsive behavior in purple phototrophic bacteria was thought to be unique to R. centenum (8,16), although some species of cyanobacteria are capable of phototaxis (5, 7).…”
mentioning
confidence: 99%
“…Purple phototrophic bacteria in liquid media reverse the direction of flagellum-driven movement in response to a sudden change in light intensity. This "Schreckbewegung" or "scotophobic" response occurs regardless of the direction of the light source, which is not phototaxis (2,8,16). Experiments on Rhodobacter sphaeroides indicated that this response to a change in light intensity requires the light-dependent catalytic activity of the photosynthetic apparatus, but the signal transduction pathway that connects this primary sensation to flagellum rotation is not known (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacteria are motile and propel themselves by rotating helical flagella driven by molecular motors (51,113). Since the initial observations of bacterial motility, a rich set of "taxes" (i.e., directional movement responses) in response to external stimuli have been identified (70), including motion directed by light (phototaxis), temperature (thermotaxis), magnetic fields (magnetotaxis), electric fields (galvanotaxis), pH (pHtaxis), oxygen (aerotaxis), and chemical cues (chemotaxis) (29,59,63,91). The most ubiquitous and best studied of these behaviors is chemotaxis (112).…”
Section: Introductionmentioning
confidence: 99%
“…A more accurate description of this phenomenon is that when smooth-swimming cells migrate into a dark region (or into regions of the spectrum where wavelengths are not absorbed by photopigments), they either tumble or reverse the direction of movement, depending on the species. The phenomenon has been termed a scotophobic (fear of darkness) response since the cells exhibit an aversion to darkness rather than a specific affinity for light (12,29). Since a reduction in light intensity causes a tumbling/reversal response, the mechanism of moving through an increasing gradient of light intensity appears to involve a directed "random walk" such that the length of smooth swimming is longer when cells are going up a light gradient than when they are going down.…”
mentioning
confidence: 99%